Weaning practices and weaning foods of Malays in Kota Bharu, Kelantan - Suppian, Nurul Munirah Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Weaning practices is crucial in providing adequate energy and nutrients to infants when breast milk can no longer acts as the primary source for adequate nutrition. WHO had recommended mothers to start weaning practices when the infants reach 6 month of age. Weaning foods selection changes over the time. Study regarding weaning food is important to see selection and preferences of weaning foods by mothers and their infants. This research aimed to describe weaning practices and types of weaning foods introduced to infants of Malays mothers in Kota Bharu, Kelantan. This study was a cross-sectional study conducted among mothers attending the five selected government health clinics in Kota Bharu, Kelantan by using purposive sampling. 1 05 respondents who completed a set of pre-tested interviewer administered questionnaire; 24-hour diet recall form and Food Frequency Questionnaires (FFQ) were included in the analysis. Findings showed that majority of 73.3% children started weaning at the age of 6 months. The mean for weaning age among infants in Kota Bharu is in parallel with WHO's recommended guidelines. The study also showed that introduction of weaning was primarily influenced by mother's instinct to start weaning, infants showing signs of hungry and advice from the surroundings. More than half of respondents (54.3%) chose to wean their children by using combination of home-made food and commercial food products rather than focusing only on one type of food. Besides that, this study found that weaning food selection pattern changes over the age. Older infants were fed primarily by home-made foods. Meanwhile commercial food product was only prevalent during the early age of weaning. The main source for weaning information was obtained from doctors and health practitioners, followed by respondent's mothers, and information on magazines or newspapers. The study showed that in daily basis, most selected food for weaning is rice, poultry, sea fish, and plain water. Meanwhile, in weekly basis, most selected foods includes chicken eggs, starchy and dark-green leafy vegetables, fruits such as bananas, apple and papaya, also biscuits and local delicacies. Legumes and milk product were seldom selected among weaning foods. There was no significant difference between maternal education and age infants started to wean, and no association was found between household income and selection of weaning food types. Weaning timing of children in Kota Bharu had good compliance with the recommendation age. Weaning food selection varies among the children, but only focus on certain food groups.